Rancang Bangun Terowongan Angin Sistem Terbuka Pada Kecepatan Angin 3 M/Detik - Meitri Nelta; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
This research was conducted to design wind tunnels that will later be used to support research burning peat soil. Wind tunnel is a subsonic type open system wind tunnel. Wind tunnel made in this study consist of several parts namely, honey comb, settling chamber, contraction, test chamber and diffuser. Size cross section testing chamber is 19.8 cm x 19.8 cm with a length of 39.6 cm. The size of the wind tunnels is adjusted to the wind speed at Riau area which is equal to 3 m/s. In testing it is seen a phenomenon wind flow that occurs and also determines the wind speed of testing chamber. At wind speeds of 3 m/s the flow phenomenon that occurs is flow laminar and speed of wind flow rate at testing chamber at 1.7 m/s.Keywords: wind velocity, open system wind tunnel